Endodermal sinus tumor of the vulva: successfully treated with high-dose chemotherapy. Issue 5 (1st August 2004) - Traen, K.; Logghe, H.; Maertens, J.; Mattelaere, C.; Moerman, P.; Vergote, I.
Abstract : Endodermal sinus tumors (EST) of the lower female genital tract are uncommon malignancies. Most of these tumors are found in the vagina or in the cervix. Only seven cases of EST involving the vulva are reported. We report an eighth case of vulvar EST. The patient recurred and was successfully treated with high-dose chemotherapy and peripheral blood cell transplantation. Because of their location, an early diagnosis of vulvar EST should be possible. Resection of the lesion by using a modified radical vulvectomy followed by cisplatin-based chemotherapy seems the best treatment for these tumors today. Our patient was initially treated with the help of local surgery and adjuvant chemotherapy consisting of three courses of etoposide and cisplatin. Sixteen months after the first diagnosis, pleural and lung metastases were diagnosed. Second-line chemotherapy followed by high-dose chemotherapy with autologous peripheral blood stem cell support was administered after resection of the lung metastases and biopsy of the pleural metastases. There is no evidence of disease 40 months after the diagnosis of the lung and pleural metastases, and 56 months after the primary diagnosis.